A system for analysis of information structure of programs. - Stefanov, C.S. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2005)
An autonomous system for analysis of information structure of programs is described. The system is intended for adaptation of sequential programs for running on parallel computing systems.